A Peranan Wakaf Produktif Dalam Membantu Perekonomian Rumah Tangga Pada Masa Covid 19 - Khairul Umam (Journal of Creative Power and Ambition (JCPA), 2025)
This study was conducted at the Ats-Tsauroh Grand Mosque, Serang, Mosque Foundation, aiming to find out how waqf land is managed as a productive business aspect that can benefit the wider community through economic empowerment, especially for business actors who sell on waqf land during the Covid19 pandemic. This study uses a descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation techniques. The results of the data are analyzed using the Miles and Huberman data model. The results of this study indicate that the Nazhir Foundation has managed land waqf at the Ats-Tsauroh Grand Mosque productively and utilized it for the benefit of the general public. Waqf land at Ats-Tsauroh Serang, the Grand Mosque has so far played a role in supporting the economic growth of business actors through productive waqf management, such as using it as land for trading activities so that business actors continue to generate income to meet their household needs during the Covid-19 pandemic. Statement of public interest.